The Motivation of Generation Z to Adopt Sustainable Fashion Practices, Including the Purchase of Secondhand Items - Sawsan Elsharkawi; Jie Sun (Environmental Science and Sustainable Development)
Generation Z (Gen-Z) consumers are becoming increasingly aware of climate change and are adjusting their fashion consumption habits towards more sustainable practices, such as thrifting, renting, and swapping. Although these practices are less common in Egypt, recent trends indicate a growing acceptance among Egyptian Gen-Z consumers. This study aims to address the limited research on fashion collaborative consumption in the Egyptian market by exploring factors influencing the adoption of secondhand and rental fashion through in-depth interviews with 20 participants. Findings show that traditional practices like borrowing clothes are prevalent for cultural and economic reasons rather than sustainability alone. Despite interest driven by economic challenges and social media, barriers like inconvenience, high costs, and limited options hinder broader adoption. To facilitate growth, enhanced shopping experiences, improved accessibility, and shifts in social attitudes are necessary, alongside support from the government and brands. This research offers valuable insights for tailoring business strategies to different consumer segments to promote sustainable fashion practices.